Active and Reactive Power Coordinated Optimal Dispatch in Active Distribution Network Considering Spatial-temporal Correlation of Wind Power. Issue 1 (March 2021) - Qu, Hanbing; Yang, Fu; Lin, Qirong; Jia, Yujian
Abstract: The high penetration of renewable energy increases the difficulty of optimal dispatch and brings challenges to the safe and economic operation of the distribution network. This paper proposed an active and reactive power coordinated optimal dispatch model, and the spatial-temporal correlation of wind power output is considered. Firstly, the copula function and non-parametric estimation methods are adopted to model the spatial-temporal correlation of wind power. Secondly, the parameters in the copula fitting function are estimated based on the maximum likelihood estimation method. Besides, the active power and reactive power outputs of various flexible resources in the active distribution network (ADN) are coordinated. The proposed model can significantly reduce the network loss of the ADN, improve efficiency, and optimize the power purchase plan. A case study on a modified IEEE 33-bus system verified the effectiveness of the proposed method.